MORAL VALUES ANALYSIS IN THE FAULT IN OUR STARS NOVEL BY JOHN GREEN - Muhammad Yusril Ihza Mahendra; Dina Amelia (Linguistics and Literature Students' Journal, 2020)
Moral Value is a value that affects individual and social behavior in behaving. The current study aimedto find the categories of moral values that John Green tries to convey in The Fault in Our Stars noveland to interpret its meaning by using the theory of Universal Moral Values by Kinnier et. al with fourmajor moral values. To be able to understand moral values in the story without misinterpretation andthe lessons can be applied in real life. This study used the qualitative method because it focuses ondescribing and interpreting the moral values in descriptive. The primary source of data is taken fromthe novel The Fault in Our Stars in the form of narrations and the secondary data is from previousstudies in the form of statements that comes from the study findings. The results of the current studyshow that the categories of moral values found in the novel are (1) Commitment to something greaterthan oneself, (2) Self-respect, but with humility, self-discipline, and acceptance of personalresponsibility, and (3) Respect and caring for others, while the moral value that is not found is (4)Caring for other living things and environment which indicates that John Green inserted moral valuesin the novel more about the personal lives of the characters and the relationships between them, whichto civilize it, readers, to have the moral as an individual, being good to other people and to believe tosomething greater.